Professional ASP.NET MVC 3 - Galloway, Jon; Lipton, Eilon (Wrox, 2011)
New edition of the top book on MVC from the top ASP.NET experts at Microsoft!MVC 3.0 is the latest update to Microsoft's Model-View-Controller technology, which enables developers to build dynamic, data-driven web sites. This in-depth book shows you step by step how to use MVC 3.0. Written by top ASP.NET MVC experts at Microsoft, the latest edition of this popular book covers new and updated features such as the new View engine, Razor, NuGet, and much more. The book's practical tutorials reinforce concepts and allow you create real-world applications. Topics include controllers and actions, forms and HTML helpers, Ajax, unit testing, and much more.Shows developers and programmers how to use ASP.NET MVC 3.0, Microsoft's new version of its Model-View-Controller technology for developing dynamic, data-driven web sitesFeatures an expert author team all are members of Microsoft's ASP.NET teamUses a step-by-step approach to explain all major features and functionalities and provides practical tutorials to allow you to create real-world applicationsGoes into theory as well as practical application and covers such topics as Razor, NuGet (PowerShell inside Visual Studio 2010), and new layout featuresMove your development skills to the next level with MVC 3.0 and Professional ASP.NET MVC 3.0.